How Do Students Use Their Mobile Devices to Support Learning? A Case Study from an Australian Regional University - Helen Farley; Angela Murphy; Chris Johnson; Brad Carter; Michael Lane; Warren Midgley; Abdul Hafeez-Baig; Stijn Dekeyser; Andy Koronios (Journal of Interactive Media in Education, 2015)
Though universities are eager to leverage the potential of mobile learning to provide learning flexibly, most balk at the cost of providing students with mobile hardware. The practice of ‘bring your own device'(BYOD) is often mooted as a cost-effective alternative. This paper provides a snapshot of student ownership of mobile devices at a regional Australian university. Our research shows that students do have access to and use a wide range of devices. However, the delivery of learning is challenged when students try to access materials and activities using these devices. Course materials are rarely optimised for use on smartphones, navigating websites and learning management systems becomes a scrolling nightmare, and interacting with other students is often impractical using prescribed systems. Most concerning is that none of the students surveyed were participating in educator-led mobile learning initiatives. The paper concludes with the proposal of some practical, low-cost tactics that educators could potentially employ to begin engaging with mobile learning, leveraging what students already do.